The multi-state energy landscape of the SAM-I riboswitch: a single-molecule Förster resonance energy transfer spectroscopy study - Manz, Christoph; Kobitski, Andrei Yu.; Samanta, Ayan; Jäschke, Andres; Nienhaus, G. Ulrich (The journal of chemical physics, 2018)
RNA (ribonucleic acid) molecules are highly flexible biopolymers fluctuating at physiological temperatures among many different conformations that are represented by minima in a hierarchical conformational free energy landscape. Here we have employed single-molecule FRET (smFRET) to explore the energy landscape of the B. subtilis yitJ SAM-I riboswitch (RS). In this small RNA molecule, specific binding of an S-adenosyl-L-methionine (SAM) ligand in the aptamer domain regulates gene expression by inducing structural changes in another domain, the expression platform, causing transcription termination by the RNA polymerase. We have measured smFRET histograms over wide ranges of Mg2+ concentration for three RS variants that were specifically labeled with fluorescent dyes on different sites. In the analysis, different conformations are associated with discrete Gaussian model distributions, which are typically fairly broad on the FRET efficiency scale and thus can be extremely challenging to unravel due to their mutual overlap. Our earlier work on two SAM-I RS variants revealed four major conformations. By introducing a global fitting procedure which models both the Mg2+ concentration dependencies of the fractional populations and the average FRET efficiencies of the individual FRET distributions according to Mg2+ binding isotherms, we were able to consistently describe the histogram data of both variants at all studied Mg2+ concentrations. With the third FRET-labeled variant, however, we found significant deviations when applying the four-state model to the data. This can arise because the different FRET labeling of the new variant allows two states to be distinguished that were previously not separable due to overlap. Indeed, the resulting five-state model presented here consistently describes the smFRET histograms of all three variants as well as their variations with Mg2+ concentration. We also performed a triangulation of the donor position for two of the constructs to explore how the expression platform is oriented with respect to the aptamer.
Gesehen am 11.10.2019